2021
DOI: 10.1016/j.mayocpiqo.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

GRIT: Women in Medicine Leadership Conference Participants’ Perceptions of Gender Discrimination, Disparity, and Mitigation

Abstract: Objective To assess demographic characteristics and perceptions of female physicians in attendance at a medical conference for women with content focused on growth, resilience, inspiration, and tenacity to better understand major barriers women in medicine face and to find solutions to these barriers. Patients and Methods A Likert survey was administered to female physicians attending the conference (September 20 to 22, 2018). The survey consisted of demographic data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A total of 4,018 studies were identified by the initial search, 580 were identified for full-text review, and 102 1,8,10,11,18,19,24–119 were included in the final analysis (Figure 1 and Supplemental Digital Appendix 2 at http://links.lww.com/ACADMED/B493). Table 1 summarizes the key characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4,018 studies were identified by the initial search, 580 were identified for full-text review, and 102 1,8,10,11,18,19,24–119 were included in the final analysis (Figure 1 and Supplemental Digital Appendix 2 at http://links.lww.com/ACADMED/B493). Table 1 summarizes the key characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of women in leadership roles has documented benefits in government and business. As of May 2020, states with female governors had fewer deaths from the COVID‐19 13 . Analysis of both global and American companies revealed that those with at least three women on the board of directors have a significantly greater financial return on investment 14 .…”
Section: Discussionmentioning
confidence: 99%
“…As of May 2020, states with female governors had fewer deaths from the COVID-19. 13 Analysis of both global and American companies revealed that those with at least three women on the board of directors have a significantly greater financial return on investment. 14 Gender equity in medical leadership should have a similar impact on medicine as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to delaying childbearing, female physicians may face inadequate support when ready to grow their family. [16][17][18][19][20][21][22] This perceived lack of support may cause women to alter their careers to accommodate childbearing. In a survey of 600 female physicians, more than 70% reported that having children had influenced their career.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to delaying childbearing, female physicians may face inadequate support when ready to grow their family . This perceived lack of support may cause women to alter their careers to accommodate childbearing.…”
Section: Introductionmentioning
confidence: 99%